Nhận thức về vai trò của giáo viên trong tổ chức hoạt động khám phá khoa học tại các trường mầm non: Nghiên cứu thực trạng tại tỉnh Tây Ninh - Trần Thị Tâm Minh, Trần Thị Tâm Minh; Trần Thị Ngọc Giàu, Trần Thị Ngọc Giàu; Nguyễn Thị Thùy Linh, Nguyễn Thị Thùy Linh; Bùi Thị Hồng Diễm, Bùi Thị Hồng Diễm (Tạp chí Giáo dục, 2026)
In early childhood education, science exploration activities play an important role in fostering children’s thinking and shaping their initial learning capacities. This study investigates teachers’ perceptions of their role in organizing science exploration activities in preschools in Tay Ninh province; data were collected through a questionnaire administered to 150 teachers and in-depth interviews with five teachers to supplement and clarify the quantitative findings. The results indicate that teachers hold very positive perceptions of the characteristics of these activities and of their own roles; however, actual implementation remains limited. Notable constraints include designing problem-based situations, flexible classroom facilitation, professional self-confidence, and mobilizing resources, which together create a “perception–practice” gap. Therefore, professional development should shift from raising awareness to strengthening practical pedagogical competencies (e.g., scenario design, scaffolding children’s thinking, and reflective practice) while also improving classroom support conditions (e.g., time, class size, and learning materials/resources).